In-Cell NMR Spectroscopy: Biomolecular Structure and Function - Burz, David S. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue examines state-of-the-art in-cell NMR spectroscopy as it relates to biological systems of increasing complexity. The compendia of research and recent innovations from prominent laboratories in the field of solid state and solution in-cell NMR spectroscopy, metabolomics and technology development are presented. The work establishes in-cell NMR spectroscopy as the premier method for determining the structures and interaction capabilities of biological molecules at high resolution within the delicately intricate interior of living cells, and the means of utilizing cells as living laboratories to directly assess the effects of exogenous and endogenous stimuli on cell physiology.]